Evaluasi Kinerja Lembaga Penjaminan Mutu Institut Agama Islam Muhammadiyah Sinjai - Nurjannah, Nurjannah; Irmayanti, Irmayanti; Mirna, Mirna (LPM IHDN Denpasar, 2021)
The purpose of the higher education quality assurance system is to ensure that all higher education standards run systematically and continue in a sustainable manner. Therefore, it is hoped that a quality culture will grow and develop in the university environment. In implementing the Quality Assurance System, Islamic Institute of Muhammadiyah Sinjai has a Quality Assurance Agency (LPM) which is tasked with implementing the SPMI. LPM as the organizer of SPMI acts as a tutor, facilitator, internal consultant, quality control and referee for the operations of all existing units. The evaluation was carried out in the form of distributing questionnaires filled out by the academic community which included the ability of LPM staff to meet document needs, the reliability of LPM staff in serving users, socialization of LPM product information, evaluation and monitoring of guidelines or standards, publication of evaluation results and monitoring of guidelines or standards, follow up evaluation and monitoring, service speed of LPM members, accuracy of service schedule implementation, and accuracy of completing tasks.